Safety, Pharmacokinetics, and Pharmacodynamics of the Oral TLR8 Agonist Selgantolimod in Chronic Hepatitis B. Issue 4 (14th September 2021) - Gane, Edward J.; Kim, Hyung Joon; Visvanathan, Kumar; Kim, Yoon Jun; Nguyen, Anh‐Hoa; Wallin, Jeffrey J.; Chen, Diana Y.; McDonald, Circe; Arora, Priyanka; Tan, Susanna K.; Gaggar, Anuj; Roberts, Stuart K.; et al.
Abstract : Background and Aims: In patients with chronic hepatitis B (CHB) infection, activation of toll‐like receptor 8 may induce antiviral immunity and drive functional cure. Selgantolimod, a toll‐like receptor 8 agonist, was evaluated in patients with CHB who were virally suppressed on oral antiviral treatment or viremic and not on oral antiviral treatment. Approach and Results: In this phase 1b study, patients were randomized 4:1 to receive either selgantolimod or placebo once weekly. Virally suppressed patients received either 1.5 mg (for 2 weeks) or 3 mg (for 2 weeks or 4 weeks). Viremic patients received 3 mg for 2 weeks. The primary endpoint was safety, as assessed by adverse events (AEs), laboratory abnormalities, and vital sign examination. Pharmacokinetic and pharmacodynamic parameters were assessed by plasma analysis. A total of 38 patients (28 virally suppressed, 10 viremic) were enrolled from six sites in Australia, New Zealand, and South Korea. Twenty patients (53%) experienced an AE and 32 (84%) had laboratory abnormalities, all of which were mild or moderate in severity. The most common AEs were headache (32%), nausea (24%), and dizziness (13%). With a half‐life of 5 hours, no accumulation of selgantolimod was observed with multiple dosing. Selgantolimod induced transient dose‐dependent increases in serum cytokines, including IL‐12p40 and IL‐1RA, which are important for the expansion and activity of multiple T‐ cell subsets and innate immunity. Conclusion: Selgantolimod was safe and well‐tolerated in virally suppressed and viremic patients with CHB and elicited cytokine responses consistent with target engagement. Further studies with longer durations of selgantolimod treatment are required to evaluate efficacy.